Efektivitas Pupuk Daun dan Dosis NPK Terhadap Produksi dan Mutu Benih Bayam Hijau (Amaranthus hybridus L.) - Absari, Kharisma Puspita; Azizah, Maria; Suwardi, Suwardi (Agropross : National Conference Proceedings of Agriculture, 2023)
Amaranthus hybridus is a plant that is popular among the public because it has high nutrition and is used as the main ingredient in industrial preparations. However, this is not balanced with the high market demand due to decreased production of Amaranthus hybridus. Thus, efforts to increase the yield of amaranthus hybridus seed production need to improve the cultivation system through the effectiveness of fertilization. This study aims to determine the effect of NPK fertilizer doses and foliar fertilizer concentrations on the production and quality of amaranthus hybridus seeds. The study was conducted from August to October 2022 at Munder, Yosowilangun, Lumajang. The experimental design used in a randomized block design consisted of two factors and 3 reaplications. The main factor is the dose of NPK fertilizer (108 kg/ha, 118 kg/ha, and 128 kg/ha) and the second factor is the concentration of foliar fertilizer (2 , 3 and 4 gram/L of water). The results showed that the doses of NPK fertilizer and the concentration of foliar fertilizer had a significant effect on plant height, seed production per hectare, and viability. The concentrations of foliar fertilizer has an significant for total branches per plant (13,85 pieces).